Psychosocial working conditions and Burnout among Healthcare Professionals in a Tertiary Care Hospital in Karachi, Pakistan. - Misha Irshad; Farah Ahmad; Syed Hassan Danish (International Journal of Endorsing Health Science Research, 2022)
Background: Healthcare professionals experience stressful working conditions that can lead to burnout. This study investigates the association between psychosocial working conditions and burnout among healthcare professionals in a tertiary care hospital in Karachi, Pakistan. Methodology: This cross-sectional study was conducted at three different facilities of Dr. Ziauddin Hospital, Karachi, from July 2021 to December 2021. Two standardized surveys were used to assess the psychosocial working conditions and burnout. The selected participants were associated with the institutional healthcare facility and were working as house officers, residents, nurses, dentists, and allied health professionals. Results: out of 384 distributed questionnaires, only 172 participants completed and returned the questionnaire. The mean score of burnouts was 46.24 with an SD value of 16.1 when assessed with the different levels of burnout (i.e., no burnout, stressed out, mild burnout, burned out, server burnout), it was found that the majority of the participants' n=56 (32.6%) had mild burnout and n=55 (32%) had burnout while severe burnout was found in n=22 (12.8%). Conclusion: Our study results indicate that there is a significant increase in healthcare professionals' level of burnout in a tertiary care system.